Rio+20 and the future of the UN sustainability architecture: what can we expect? - Steffen Bauer; Silke Weinlich (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
Two issues will take centre stage at the forthcoming UN Conference on Sustainable Development (Rio+20): the prospects for a global “green economy” in the context of poverty alleviation and sustainable development, and the United Nations' institutional framework for sustainable development. In the run-up to the conference, public attention is heavily focused on the issue of a green economy and the formulation of global Sustainable Development Goals (SDGs). But the development of the UN's institutional sustainability architecture must not be treated as a secondary issue. It is indeed a precondition if the visionary green economy ideas are to become tangible for the day-to-day business of multilateral development cooperation and if any SDGs that may emerge are to be achieved. At the very least Rio+20 should therefore provide the framework in which the heads of state and government admit to the world public once and for all that the alleged conflict between environment and development is a construct that must be overcome to everyone's benefit. Global development that is sustainable in the true meaning of the word will remain impossible unless scarce natural resources are used responsibly and unless climate change is effectively mitigated. Effective environment policy and forward-looking resource management, on the other hand, will help, especially under conditions of poverty, to improve the well-being and development prospects of the people affected. The prospective realignment of the UN environment and development institutions thus becomes a litmus test of the United Nation's future ability to take action in the realm of sustainable development and a gauge of how seriously the international community takes the goal of transforming the global economy. A highranking Council for Sustainable Development and an environment agency that carries more political weight may be instrumental in this, so long as they are not restricted to symbolic policies. This calls for unequivocal political support from the heads of state and government, international agreement on the development of more efficient negotiating and decision-making processes, more effective instruments for implementation and supervision and reliable financial resources on an adequate scale. Any new or reformed agency must fit into the overall UN institutional structure and take account of reforms already being undertaken to achieve “system-wide coherence”. Only then can the United Nations be put in a position to provide the enduring support expected of it for a global transformation to sustainable development.
Keywords: 330